Sustainability of improvements in irrigation management - Gopinath, C.; Kalro, A. H. (International Food Policy Research Institute, 1990)
India, in common with the rest of South Asia, has seen rapid strides in irrigation development in the past few decades. The expansion and improvement of irrigation facilities occupy a prominent place in India's programs for agricultural development. The financial outlays and expenditures incurred on development of major, medium, and minor irrigation in the country's five-year plans are given in Table 13.1. As Oesai's chapter in this volume (Chapter 4) shows, despite the sizable nature of the investments incurred in the irrigation sector, there has been over the years a persistent gap between irrigation potential and its use.